A study on the correlation between HPV DNA and IHC P16 expression in cervical lesions - WANG Haochen, JIA Liqing, YANG Yu, WANG Qian, YU Chengli, TIAN Tian, BI Rui, TU Xiaoyu, BAI Qianming, ZHU Xiaoli, ZHOU Xiaoyan, REN Min (Zhongguo aizheng zazhi)
Background and purpose: Human papilloma virus (HPV) infection status is crucial for diagnosing cervical precancerous lesions and classifying cervical cancer. High-risk (HR) HPV is often linked to P16 protein overexpression, so P16 detection via immunohistochemistry (IHC) is commonly used to assess HPV infection. However, the differences between HPV status and P16 expression remains unclear. An in-depth study of the correlation between HPV and P16 is essential for clinical guidance. Methods: We retrospectively collected clinical and pathological data of cervical lesions from 618 patients diagnosed at the Department of Pathology, Fudan University Shanghai Cancer Center from January 2020 to December 2023 (Ethical number: 050432-4-2307E). Polymerase chain reaction (PCR) reverse dot hybridization was used to detect HPV including HR and low-risk (LR) subtypes, and immunohistochemistry was used to detect P16 for comparative analysis. Based on different clinical and pathological diagnoses, the sensitivity and specificity of P16 expression in evaluating HPV infection were evaluated. Among the 618 cases of cervical lesions, there were 92 cases of cervical squamous cell carcinoma, 257 cases of cervical adenocarcinoma, 79 cases of high-grade squamous intraepithelial lesions (HSIL), 105 cases of low-grade squamous intraepithelial lesions (LSIL), and 85 cases of chronic cervical inflammation. Results: According to clinical diagnosis, the HR-HPV positive rate in cervical squamous cell carcinoma was 88.0% (81/92), the P16 positive rate was 91.3% (84/92), and the overall consistency rate between P16 and HPV detection was 90.2% (88/92); for HR-HPV infection, the sensitivity and specificity of P16 were 96.3% and 45.5%. The positive rate of HR-HPV in adenocarcinoma was 54.5% (140/257), the positive rate of P16 was 58.8% (151/257), and the overall consistency rate between P16 and HPV detection was 82.5% (212/257); for HR-HPV infection, the sensitivity and specificity of P16 were 87.9% and 76.1%. In HSIL, the HR-HPV positive rate was 75.9% (60/79), the positive rate of P16 was 70.9% (56/79), and the overall consistency rate between P16 and HR-HPV detection was 82.2% (65/79); for HR-HPV infection, the sensitivity and specificity of P16 were 85.0% and 73.7%. In LSIL, the HR-HPV positive rate was 73.3% (77/105), the positive rate of P16 was 8.5% (9/105), and the overall consistency rate between P16 and HR-HPV detection was 33.3% (35/105); for HR-HPV infection, the sensitivity and specificity of P16 were 10.4% and 96.4%. In chronic cervical inflammation, the HR-HPV positive rate was 20% (17/85), the positive rate of P16 was 0.0% (0/85); for HR-HPV infection, the sensitivity and specificity of P16 were 0.0% and 100.0%. There was a significant positive correlation between P16 positivity and HPV16/18 in cervical squamous cell carcinoma, adenocarcinoma, and HSIL (P=0.000), while there was no significant correlation in LSIL and chronic cervical inflammation (P>0.05). Conclusion: In cervical squamous cell carcinoma and adenocarcinoma, the consistency of P16 expression and HPV DNA positivity are high, especially in HPV16/18 subtype. There is a good concordance between HR-HPV positivity and P16 protein overexpression. The positive expression of P16 in HSIL may initially reflect HPV infection status. However, in LSIL and chronic cervicitis, P16 expression may not accurately correlate with HPV infection. The inconsistency between P16 and HPV DNA testing could be influenced by multiple factors, including HPV subtypes, histopathological categories, specimen quality, and technical limitations. In clinical practice, it is recommended to conduct comprehensive analysis or employ multiple diagnostic methods to confirm HPV infection status for precise evaluation.